Discrete resistive switching characteristics in metal-free phthalocyanine and Dy-phthalocyanine based devices. (March 2022) - Ruan, Liuxia; Tong, Junwei; Luo, Feifei; Wu, Yanzhao; Qin, Gaowu; Zhang, Xianmin
Abstract: The resistive memory devices based on planar metal-free phthalocyanine (H2 Pc) and sandwiched Dy-phthalocyanine (DyPc2 ) have been prepared on an ITO glass substrate with the Al as a top electrode. The current-voltage characteristics of these devices are found to be relevant with the interlayer thickness and the crystalline structure. Both the average values of reset and set voltage increased with the increasing thickness of interlayer. The devices can be cycled more than 150 consecutive cycles when the thickness of H2 Pc and DyPc2 are 60 nm and 30 nm, respectively. The resistances of present H2 Pc devices are larger than that of DyPc2 devices, which may be related to different orientations of H2 Pc and DyPc2 films. Additionally, a high ON/OFF current ratio of about 10 3 and a long retention ability of over 10 4 s were achieved for both devices, implying their nonvolatile storage capacity. An analysis of the current-voltage characteristics revealed that the electrical conduction behavior followed the space charge limited conduction mechanism. This study is useful to design advanced resistive memory devices and understand the underlying resistive switching mechanism. Highlights: ITO/H2 Pc/Al and ITO/DyPc2 /Al devices were prepared with different interlayer thicknesses using a vacuum deposition system. Both devices showed more than 150 consecutive cycles when the thicknesses of H2 Pc and DyPc2 were 60 nm and 30 nm, respectively. A high ON/OFF current ratio of about 10 3 and a long retention ability of over 10 4 s were achieved. The electrical conduction behavior of the devices followed the space-charge-limited current mechanism.